2004
DOI: 10.1111/j.1600-079x.2004.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin ameliorates chronic renal failure‐induced oxidative organ damage in rats

Abstract: Chronic renal failure (CRF) is associated with oxidative stress that promotes production of reactive oxygen species (ROS). Melatonin, the chief secretory product of the pineal gland, was recently found to be a potent free radical scavenger and antioxidant. The aim of this study was to examine the role of melatonin in protecting the aorta, heart, corpus cavernosum, lung, diaphragm, and kidney tissues against oxidative damage in a rat model of CRF, which was induced by five of six nephrectomy. Male Wistar albino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 52 publications
5
40
0
1
Order By: Relevance
“…Apart from the major enzymatic antioxidants, such as superoxide dismutase, GSH peroxidase, and catalase, estrogens are also classified as nonenzymatic antioxidants that delay or inhibit age-associated pathological and biological changes. [57] Several experimental studies have shown that antioxidant capacity of tissues is decreased in animals with CRF, [58,59] while marked reductions in plasma glutathione concentration and glutathione peroxidase activity, as well as marked increases in the ratios of oxidized to reduced GSH were observed in CRF patients. [60,61] Current findings show that the reduction in GSH content of the studied tissues of male and ovariectomized rats may be due to its consumption during CRF-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the major enzymatic antioxidants, such as superoxide dismutase, GSH peroxidase, and catalase, estrogens are also classified as nonenzymatic antioxidants that delay or inhibit age-associated pathological and biological changes. [57] Several experimental studies have shown that antioxidant capacity of tissues is decreased in animals with CRF, [58,59] while marked reductions in plasma glutathione concentration and glutathione peroxidase activity, as well as marked increases in the ratios of oxidized to reduced GSH were observed in CRF patients. [60,61] Current findings show that the reduction in GSH content of the studied tissues of male and ovariectomized rats may be due to its consumption during CRF-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…12 It was established that formation of free radicals, which were induced by several stimuli in renal tissue was prevented by melatonin. 13,14 Likewise, it is indicated that as a result of pinealectomy to remove the main source of melatonin, increases of lipid peroxidation in tissues occurs.…”
mentioning
confidence: 99%
“…These results also are in a harmony with the recorded data by Macdonald et al (2003) explained the oxidative stress occurs when a balance is disrupted by excessive production of Reactive Oxygen Speacies (ROS), including superoxide, hydrogen peroxide and hydroxyl radicals and/or by inadequate antioxidant defenses, including suboptimal levels of catalase, Glutathione Peroxidase (GPx), vitamins C and E and reduced glutathion. Sener et al (2004) found that in the erythrocytes of male Wistar albino rats at 4 weeks after 5/6 nephrectomy, GPx activity was found to be reduced, in addition Devinder et al (2004) found that the glycerol treated group showed depletion in antioxidant system which indicated by the significant decrease in the levels of glutathione reductase and superoxide dismutase enzymes. Pandir and Kara (2013) clarified that Superoxide Dismutase (SOD), catalase (CAT) and Glutathione Peroxidase (GPx) activities were decreased and malondialdehyde MDA levels were increased in the cisplatin nephrotoxicity group.…”
Section: Discussionmentioning
confidence: 99%